Linking Economic and Industrial Development to Urbanization: Case of Dholera Special Investment Region-Gujarat (International Journal of Innovative Research in Engineering & Management, 2022)
In the last two decades, post  Industrialization cities have been conceived as product of  global aspiration and identity. This paper attempts to  understand the transformative model of governance  adopted in development of the Dholera Special Investment  Region in the domain of private partnership and exclusive  planning strategies. It explores the role of speculation and  making the city a spectacle in the planning of Dholera  Special Investment Region. Working on the intersection of  these broad theories of the mode of governance, it analyses  the Special Investment Region Act, as a facilitator to the  growth corridor project and investigates the role of the  State in the conceptualization and execution of mega project. The greenfield project reflects the transnational  circular economy and urban policies that have brought a  paradigm shift in the planning and development of cities in  Neo-Liberal Era. It investigates the implications of SIR  Act, 2009 on a greenfield project in reference to the right  to the city. It argues that for the case of Special Investment  Region, Urbanization is seen as a byproduct of the  transformative economic and industrial policies.
Keywords: Dholera Special Investment Region; Greenfield; Special Investment Region; Worlding strategy